2002
DOI: 10.1016/s1097-2765(02)00660-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling of Capping and Transcription of mRNA

Abstract: In humans, 5' m(7)G cap addition is accomplished cotranscriptionally by the sequential action of the capping enzyme (Hce1) and the cap methyltransferase (Hcm1). We found that guanylylation and methylation occur efficiently during transcription with t(1/2)'s of less than 15 and 70 s, respectively. A two to four order of magnitude increase was found in the rate of guanylylation of RNA in transcription complexes compared to free RNA. This stimulation required only the RNA polymerase II elongation complex and Hce1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
131
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 42 publications
9
131
0
Order By: Relevance
“…In the past few years successful attempts were made to develop systems that coupled transcription and capping (Moteki and Price 2002), as well as transcription and polyadenylation (Adamson et al 2005;Rigo et al 2005). In vitro systems that combine transcription and splicing have also been described (Ghosh and GarciaBlanco 2000;Ibrahim et al 2005;Das et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years successful attempts were made to develop systems that coupled transcription and capping (Moteki and Price 2002), as well as transcription and polyadenylation (Adamson et al 2005;Rigo et al 2005). In vitro systems that combine transcription and splicing have also been described (Ghosh and GarciaBlanco 2000;Ibrahim et al 2005;Das et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The cleavage site was 180 bp downstream of the start site of transcription and was followed by about 900 bp of template that could be used to stall polymerases after they had passed the site of processing. The cytomegalovirus promoter was chosen because it has been extensively used to study the function of the elongation control factors, P-TEFb, NELF, and DSIF (29,30), a termination factor, TTF2 (31), and the functional coupling of the capping enzyme, HCE, with transcription (27).…”
Section: Resultsmentioning
confidence: 99%
“…One such human system was used to examine capping during transcription and it was found that the transcription complex had a profound influence on the capping reaction (27). We have adapted that transcription system to the study of polyadenylation and have begun to define parameters of the coupling process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Capped pol II transcripts as short as 25-40 bases are made in transcription extracts and isolated nuclei suggesting that capping is a very early co-transcriptional event 14 -17. Both HCE and MT can bind directly to pol II that is phosphorylated on the CTD 18 but in vitro studies suggest that these interactions with actively transcribing pol II are weak 16,17 , and their in vivo significance remains unknown.…”
Section: Introductionmentioning
confidence: 99%